Study on extraction technology and antioxidative activity of polysaccharides produced by Lachnum hyalopus - YE Ming; LI Shi-yan; YANG Liu; ZHU Li; LIN Ying-ren (浙江大学学报. 农业与生命科学版)
Extraction of polysaccharide from Lachnum hyalopus with microwave and its scavenging capacity of superoxide anion radical and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical were studied. The results indicate that the optimum conditions for extraction of polysaccharide were as follows: microwave power was 150 W with ratio of liquid to material at 80 and 3 min of extraction time. Under above conditions, the polysaccharide yield was up to 12.05%. Meanwhile, the scavenging effects of the polysaccharide on O2- and DPPH free radicals were both significant, which the scavenging effects on the O2- radical reached 86, 67% with 100 mg·L-1 polysaccharide, and the clearance rate of DPPH free radical reached 10.79% with 10 mg·L-1 polysaccharide. So it can be concluded that the polysaccharide displayed obvious antioxidant activities.